The Short Life and Resurrection of SEC Rule 19C-4 - Stephen M. Bainbridge (Washington University Law Quarterly, 1991)
After a brief description in Part I of dual class capital structures, Part II of this Article evaluates rule 19c-4 and the Commission's arguments as to the need for regulation of dual class stock. In essence, the Commission argued that shareholders were being forced to accept certain types of dual class transactions without having any meaningful voice in the matter. Part II demonstrates that dual class transactions are objectionable not because of these so-called collective action problems, but because of the conflict of interest inherent in management's decision to propose such transactions. Once dual class stock is seen as a conflict of interest problem, the question arises as to whether the SEC had authority to adopt rule 19c-4. Conflict of interest transactions traditionally are a matter of state law; indeed, rule 19c-4 was the SEC's first substantive regulation of conflict of interest transactions generally applicable to public corporations. More generally, it also was the SEC's most direct regulation of corporate governance to date. In June 1990, the United States Court of Appeals for the District of Columbia invalidated rule 19c-4 on the grounds that the Commission had exceeded the statutory authority delegated to it by Congress. Part III argues that the court of appeals' decision was correct in light of the Exchange Act's literal language, its legislative history, and its historical context. Part III concludes by examining some of the broader implications of the D.C. Circuit's opinion for future SEC regulation of corporate governance, proxies, and takeovers. Because the SEC decided not to seek en banc or Supreme Court review of the D.C. Circuit panel's decision, the battleground has shifted back to the states and the SROs. As of this writing, two of the principal SROs have adopted listing standards modeled on rule 19c-4. Part IV of this Article argues that the SROs are an appropriate forum in which to address the conflict of interest potentially present in dual class transactions, but that simply grafting rule 19c-4 into SRO listing standards is the wrong answer to the problem. Instead, Part IV offers an alternative regulatory scheme.
Keywords: Stockholders& #x27; voting